2018
DOI: 10.1097/meg.0000000000001180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and hepatitis C infection from a population-based study in Southern India

Abstract: The prevalence of HBV was 1.63% and HCV was 0.30% in Tamil Nadu. Three-fourths of HBV/HCV infected people were males. Prevalence of HBV/HCV was higher in rural areas. Slum area and dialysis unit had high HBV and HCV prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
10
3
Order By: Relevance
“…They have also been used in mass screening programs for hepatitis B in both community outreach [ 24 , 57 ] and health-facility-based screening [ 52 , 53 , 58 , 59 , 60 , 61 , 62 ] in low-resource settings and shown great public health benefits. For example, in a community-based outreach screening program conducted in 75 camps in Southern India [ 63 ], the “screen and vaccinate/linkage to care” strategy led to over 7700 vaccinations in the camps and 162 people with high viral load getting treatment. The program increased the accessibility of hepatitis B diagnostic testing in a low-resource setting, and the timely results of POCs contributed to people’s engagement in post screening interventions [ 63 ].…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
See 2 more Smart Citations
“…They have also been used in mass screening programs for hepatitis B in both community outreach [ 24 , 57 ] and health-facility-based screening [ 52 , 53 , 58 , 59 , 60 , 61 , 62 ] in low-resource settings and shown great public health benefits. For example, in a community-based outreach screening program conducted in 75 camps in Southern India [ 63 ], the “screen and vaccinate/linkage to care” strategy led to over 7700 vaccinations in the camps and 162 people with high viral load getting treatment. The program increased the accessibility of hepatitis B diagnostic testing in a low-resource setting, and the timely results of POCs contributed to people’s engagement in post screening interventions [ 63 ].…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
“…For example, in a community-based outreach screening program conducted in 75 camps in Southern India [ 63 ], the “screen and vaccinate/linkage to care” strategy led to over 7700 vaccinations in the camps and 162 people with high viral load getting treatment. The program increased the accessibility of hepatitis B diagnostic testing in a low-resource setting, and the timely results of POCs contributed to people’s engagement in post screening interventions [ 63 ]. The HBsAg POCs were also used in programs to engage hard-to-reach populations such as people who inject drugs, sex workers [ 64 ], disadvantaged groups or some ethnic groups [ 65 , 66 ] by providing self-testing, community or health-facility-based testing services.…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Shanmugam et al found that the prevalence of HBV was 1.63% and prevalence was higher in rural areas. 14 Therefore, we selected random villages in the chengalpattu district of Tamil Nadu to explore the knowledge, awareness and practices related to HBV among the general population.…”
Section: Resultsmentioning
confidence: 99%
“…3 Hepatitis B, being a vaccine-preventable disease, provides an opportunity for screening to estimate the disease burden, identify risk factors and strategise adequate public health measures. 4 The goals set by WHO for the elimination of hepatitis B by 2030 include achieving the target of 90% reduction in incidence and a 65% reduction in the number of related deaths from a 2015 basline. 1 Working towards elimination and control of viral hepatitis, a National Viral Hepatitis Control Programme was launched.…”
Section: Introductionmentioning
confidence: 99%